Komposisi mineral cangkang kerang mutiara Pinctada margaritifera di Sulawesi Utara - Kalesaran, Ockstan J.; Lumenta, Cyska; Rompas, Rizald; Mamuaya, Gybert (Universitas Sam Ratulangi, 2018)
This study aimed to analyze the chemical composition of the Pinctada margaritifera shells in North Sulawesi. Shells were collected from 3 (three) locations, namely: the coast of Arakan Minahasa Selatan waters, Bahoi Minahasa Utara waters and Talengen waters of Sangihe Islands, North Sulawesi. Three samples of shell powder each containing 100 grams, packed in a plastic bag to be analyzed using the ICP-OAS type Thermo scientific iCAP 6000 Series at the Wln (Water Laboratory Nusantara) Laboratory in Manado. The shell of P. margaritifera had macro mineral composition, namely calcium, phosphorus, magnesium, sodium and micro minerals, namely manganese and iron.Keywords: Shells, Pinctada margaritifera, Mineral